Good Work, Secret Seven - Blyton, Enid (London Hodder Children's Books, 2004)
The Secret Seven feature in this centenary edition, published in its original form to commemorate the centenary of Enid Blyton's birth
Keywords: Children's Literature - Fiction : Adventure